Iris Information Management in Object-Relational Databases - Alvez, Carlos E. (2015)
Biometrics is a technology under development that has been enhanced by the increasing security concerns in organizations at all levels. Public agencies that employ this technology need to consult the biometric data efficiently and share them with other agencies. Hence the need for data models and standards that allow interoperability between systems and facilitate data searches. The objective of this work is to develop a generic architecture using object-relational database technology (ORDB), according to international standards, for identifying people by means of iris recognition. In addition, a model expressed in Unified Modeling Language (UML) class diagram where the domain data types defined for use in architecture is proposed. This architecture will allow interoperability between organizations efficiently and safely.